Dissections in Phoebe Gloeckner’s A Child’s Life (1998, 2000) - Hélène Tison (Sillages Critiques)
Phoebe Gloeckner’s anatomical drawings and écorchés, her often blunt and jarring graphic narratives centered on abusive relations, are inevitably controversial; they fly in the face of feminist attacks on such representations as debasing to women and they complexify and redirect the debate about child sexuality. But A Child’s Life cannot be summed up in terms of exploitative objectification of women’s bodies, despite the depictions of scenes of abuse and self-abuse. Gloeckner creates characters, notably a semi-autobiographical persona, who assume very different, sometimes contradictory, roles and positions, and her insistent and minute lifting of the skin of (mainly female) bodies can be read as an empowering gesture of displacement and repositioning, one that, through repetitions and variations, redirected gazes, erotic or pornographic scenes, engages the reader/viewer in a very direct, embodied manner.